Presidential Powers in Determining and Implementing an Economic Emergency: An Indonesian Constitutional Law Perspective - Intansevina; Halomoan Freddy Sitinjak Alexandra; Pujo Widodo (Journal of Innovative and Creativity, 2026)
The sustainability of national economic development faces various non‑military threats such as global economic crises, financial system turbulence, and pandemics, which demand swift and extraordinary responses from the President as the holder of executive power under the 1945 Constitution of the Republic of Indonesia. In this context, presidential powers to determine and implement policies in emergency situations become strategically important, although explicit regulation of an “economic emergency” is not clearly found in the current statutory framework. This study aims to analyse the regulation and practice of presidential powers in determining and implementing an economic emergency under Indonesian constitutional law, and to formulate an ideal construction of such powers that remains consistent with the rule of law and the protection of citizens’ constitutional rights. This research employs a normative juridical method with statutory, conceptual, and case approaches, based on the 1945 Constitution, Government Regulation in Lieu of Law Number 23 of 1959 on State of Emergency, regulations on state finance in times of crisis, and literature on emergency constitutional law. The findings reveal a normative gap concerning parameters and limits of presidential powers in an economic emergency, which opens room for power expansion potentially undermining constitutionalism. This study proposes a model for the construction of presidential powers in an economic emergency that specifies indicators, procedures, temporal and material limits, and oversight mechanisms by other state institutions, ensuring that emergency powers are exercised within the framework of the rule of law.